2001
DOI: 10.1177/000313480106700314
|View full text |Cite
|
Sign up to set email alerts
|

Age is Not a Contraindication to Pancreaticoduodenectomy

Abstract: The incidence of pancreatic cancer has increased threefold over the last 40 years with the greatest rate of growth occurring in the elderly. In the past it was suggested that elderly patients tolerated pancreaticoduodenectomy less well than younger patients with higher mortality rates. This single-institution experience examines the question of whether age is a significant factor in relation to morbidity and mortality in patients undergoing pancreaticoduodenectomy. Between 1994 and 1999 outcomes of 122 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Whereas these criteria are somewhat standard, it remains a matter of debate whether age should be considered as a contraindication to PD. Some authors have assessed the outcomes of open PD in an elderly population and found encouraging results in terms of morbidity and mortality [10][11][12][13][14][15]. For laparoscopic PD, however, a recent review of the literature [1] found a mean age of 59 years among series (range, 43-71 years).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas these criteria are somewhat standard, it remains a matter of debate whether age should be considered as a contraindication to PD. Some authors have assessed the outcomes of open PD in an elderly population and found encouraging results in terms of morbidity and mortality [10][11][12][13][14][15]. For laparoscopic PD, however, a recent review of the literature [1] found a mean age of 59 years among series (range, 43-71 years).…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic resection is a challenging surgery with high morbidity rate and some mortality. Experiences from single high-volume institutions showed that age was not a predictor of perioperative morbidity and mortality [23–25] . Age alone seems no longer an absolute contraindication for pancreatic surgery, provided appropriate counselling of elderly patients about complications that leads to prolonged convalescence [14,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Experiences from single high-volume institutions showed that age was not a predictor of perioperative morbidity and mortality. [23][24][25] Age alone seems no longer an absolute contraindication for pancreatic surgery, provided appropriate counselling of elderly patients about complications that leads to prolonged convalescence. [14,26] In reasonable risk elderly patients, benefit of pancreatic resection does not decrease with age, moreover, once patients over 80 years have passed the 2-year survival mark without cancer recurrence, their survival is similar to their age-matched counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…There are various biochemical definitions of pancreatic leakage, such as drainage of Ն 50 ml amylase-rich fluid on or after POD 10 [2,4], drainage of Ն 50 ml amylase-rich fluid (more than three times the normal plasma level) on or after POD 7 [5,12,19], drainage of more than 50 ml with the amylase level more than twice the serum amylase value [6], drainage of more than 1000 U/L of amylase-rich fluid on or after POD 7 [13], drainage with an amylase level of more than 10,000 U/L [14], drainage of more than 30 ml amylase-rich fluid on or after POD 7 or the continued use of an intraoperatively placed drain at the time of discharge regardless of the postoperative day or amount [16], drainage of more than 30 ml amylase-rich fluid (> 5000 U/L) for more than 10 days [17], drainage of more than 50 ml amylase-rich fluid (> 10,000 U/L) for more than 10 days [18], a drain amylase level more than three times the serum amylase value on the first day of feeding [20]. Without a universal definition that truly reflects pancreatic leakage, the leakage rate of a pancreaticoenterostomy may be misinterpreted and cannot be compared with others.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the drainage fluid should be rich in amylase when pancreatic juice is leaked out through the pancreaticoenterostomy. Therefore, "amylase-rich" drainage has been one of the most popular definitions of pancreatic leakage used in the literature [2,4,5,[12][13][14][16][17][18][19][20][21]. Unfortunately, the combination of different drainage amylase levels, drainage volumes, and times of measurement often makes comparison of pancreatic leakage impossible among reports.…”
mentioning
confidence: 99%